(untitled) (Journal of Civil Engineering Researchers, 2022)
The use of steel shear wall in engineering construction, including high-rise building projects that bear high lateral forces, is of great importance and practical. Since the steel shear wall with opening may have some pre-cracks due to initial damage and cause the weak lateral behavior of the shear wall, in this study, the simultaneous impact of pre-crack and opening in the three-story and one-span frame with steel shear wall has been evaluated. In this study, 48 numerical samples have been studied using the finite element method and Abaqus software. Axial and lateral loading has been applied to the samples, and the parameters of the pre-crack position, pre-crack length and the type of shear wall steel sheet material have been investigated. The results of this study demonstrated that the numerical model made for the shear wall provides reliable answers compared to the laboratory model. In the shear walls under study, the parameter of crack length and crack position has a high impact on the ductility capacity, while it has little impact on the hardness and strength index. The most critical pre-crack modes in the horizontal position, located at the top or bottom corner of the frame, have had a great impact on the lateral behavior and reduced ductility by 60% and wall strength by 32%. On the other hand, by changing the materials of the shear wall steel sheet from LYP steel to St37 and St52, the final strength and hardness have increased by 3.63 and 1.45 times, respectively and the ductility has decreased by30%.